PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA - Septian Nurrachman; Tri Jalmo; Rini Rita T. Marpaung (Universitas Lampung, 2013)
The purpose of this study to determine the effect of the TPS learning model to increase Critical Thinking Skills and students learning activities toward subject matter of Circulatory System at class XI IPA SMA Negeri 1 Natar. The research design was pretest-posttest non-equivalent groups. The samples in this study are the students class XI IPA2 and XI IPA4 randomly selected by purposive sampling technique. Quantitative data obtained from the average value of pretest and posttest were statistically analyzed using u-test. Qualitative data in the form of student activity data during the learning process. The The results showed that the use of TPS learning model there are significant effect improving Critical Thinking Skills students, it’s seen in the experimental class average N-value gain of 47.8 and an average value of N-gain control grade of 21.5 . Then the average yield of all activities of the students stated that activity in the classroom using TPS learning model each meeting higher. It’s can be concluded that the use of the TPS learning Model can improve Critical Thinking Skillsand activities of the student class XI IPASMA Negeri 1 Natar District, South Lampung toward subject matter of Circulatory System.